World Haptics 2009 - Third Joint EuroHaptics Conference and Symposium on Haptic Interfaces for Virtual Environment and Teleoper 2009
DOI: 10.1109/whc.2009.4810829
|View full text |Cite
|
Sign up to set email alerts
|

The impact of feedback design in haptic volume visualization

Abstract: Enhancing volume visualization with additional cues from our sense of touch has shown the potential to increase both speed and accuracy in the data exploration. Research in the area display a wide array of modes of interaction and many of these have been evaluated to demonstrate their capabilities. There are, however, few studies performed that compare different approaches for their strengths and weaknesses and there is a lack of guidelines on how the haptic feedback should be designed to allow for best perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…It confirmed that adding force feedback was useful for information and guidance and contributed to the understanding of the distributed flow; they concluded that "haptic feedback was considered helpful and the combination of haptics/graphics produced a better result than using visual feedback alone" [131]. Recently, Palmerius and Forsell [132] also tested three different haptic metaphors (line, surface and force) representing volumetric vector data to identify faint structures. The experiment conducted with 12 participants showed that the line and the surface metaphors permit the user to better identify faint structures in comparison to the force metaphor.…”
Section: A Scientific Visualization Diagramsmentioning
confidence: 88%
See 1 more Smart Citation
“…It confirmed that adding force feedback was useful for information and guidance and contributed to the understanding of the distributed flow; they concluded that "haptic feedback was considered helpful and the combination of haptics/graphics produced a better result than using visual feedback alone" [131]. Recently, Palmerius and Forsell [132] also tested three different haptic metaphors (line, surface and force) representing volumetric vector data to identify faint structures. The experiment conducted with 12 participants showed that the line and the surface metaphors permit the user to better identify faint structures in comparison to the force metaphor.…”
Section: A Scientific Visualization Diagramsmentioning
confidence: 88%
“…[33]). Palmerius [132] writes on haptic interaction design saying that it is useful to "not only design the feedback to most effectively convey the information, but to convey it in an intuitive manner so not to confuse the user". In particular choosing the right hardware (haptic device) is also important and can affect the users' perception of the information.…”
Section: Discussionmentioning
confidence: 99%